Synthesis and characterization of alumina membranes by sol-gel technique - Idrees, M; Sathiavathy, D; Saidi, Hamdani (1995)
The aim of this study was to determine the optimum conditions for sol preparation and to produce supported and unsupported alumina membranes. The membranes were characterized in term of their morphology and pore size by using Scanning Electron Microscope (SEM). Result obtained showed that supported alumina membranes by sol-gel technique could be prepared.